Study on Variation Characteristics and Annual and Temporal Patterns of Water and Sediment in the Yellow River - Zhang, Tongjian (Transactions on Computer Science and Intelligent Systems Research, 2025)
The Yellow River, known as the mother river of the Chinese nation, the study on the variation patterns of its water and sediment flux holds significant theoretical guiding significance for the environment, climate, people's livelihood, and optimal allocation of water resources. This paper first focuses on the annual characteristic evaluation of sediment concentration and water-sediment flux in the Yellow River. Through the analysis of actual monitoring data from the Yellow River hydrological station over the past six years, it is found that sediment concentration has significant correlations with time, water level, and water discharge. On this basis, a multiple linear regression model between sediment concentration and water discharge is established using the stepwise regression method. Based on this model and the calculation relationship between total water discharge and total sediment discharge, the annual total water discharge of the hydrological station in the past six years (2016-2021) is estimated to be approximately 197.952 billion m³, and the annual total sediment discharge is approximately 1211.364 billion kg.Subsequently, this paper delves into exploring the temporal variation patterns of water and sediment flux in the Yellow River. The M-K test method is used to analyze the mutation of monthly data of water discharge and sediment discharge over the past six years. The results show that the overall water discharge and sediment discharge exhibit a trend of slow fluctuation first and then significant increase, with the substantial growth mainly occurring after 2018. Through the seasonal decomposition model, the seasonal characteristics of water and sediment flux are revealed, which significantly increase in spring and summer and gradually decrease in autumn and winter. To further identify its periodicity, a wavelet analysis model is established, which clarifies that the variation period of water and sediment flux is one year. These research results provide a scientific basis for the management of water and sediment in the Yellow River and future trend prediction.
Keywords: Linear regression; M-K mutation test; Seasonal decomposition.